2019
DOI: 10.33564/ijeast.2019.v04i04.049
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Resolve Heterogeneity Using RPC in Client Server Systems

Abstract: The Client-Server model basic is to circulate processing and is a response to the defects conveyed by the centralized Client-Server model. The mix of information and administrations in this paper are given by Client Server design where the customers are permitted to be isolated from inborn complexities. As the principle parts in this model, client, server and system can be spoken to in the types of 2 layered and 3 layered Client Server (CS) design. The rising improvement in CS frameworks are figured out as to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…However, many hardware and software reliability models have been proposed to tackle hardware and software failures in recent decades. For instance, Garg (2019) provided a method for resolving heterogeneity in server-client systems utilizing Remote Procedure Call (RPC). Potapov et al (2019) used the Markov process to construct mathematical models for analyzing a system with a client-server architecture.…”
Section: Introductionmentioning
confidence: 99%
“…However, many hardware and software reliability models have been proposed to tackle hardware and software failures in recent decades. For instance, Garg (2019) provided a method for resolving heterogeneity in server-client systems utilizing Remote Procedure Call (RPC). Potapov et al (2019) used the Markov process to construct mathematical models for analyzing a system with a client-server architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Yusuf et al (2020) examined multicomputer system analysis consisting of three subsystems for different types of failure rates and two types of repair (General repair and Gumbel-Hougaard family copula) approaches. Garg et al (2019) studied k-out-of-n: G system and concluded that a k-out-of-n: G system is a mirror image of the k-out-of-n: F system. A case study for the train operation system was illustrated for reliability analysis and optimal design.…”
Section: Introductionmentioning
confidence: 99%
“…Ivanović et al (2017) discussed the effect of system design on the performance of client-server side software agent. Garg et al (2019) presented an approach in solving heterogeneity in client-server system.…”
Section: Introductionmentioning
confidence: 99%